Sport Massage Method Training as an Effort to Increase Active Lifestyle Awareness of Productive Age Women - Nida’ul Hidayah; Ridha Mustaqim; Widi Kusumah (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This community service programme aims to increase awareness of healthy lifestyles in productive-age women through training in the sport massage method. The partner in this activity is the Regional Leadership of Aisyiyah Bandung City, an organisation that has concerns for women's health and welfare. The training was designed to provide an in-depth understanding of the importance of physical health, especially through sport massage, which can help reduce muscle tension, improve blood circulation, and restore the body's condition after physical activity. As such, the training is expected to foster awareness of the importance of adopting a healthy and active lifestyle among women of productive age, ultimately contributing to the improvement of their quality of life. The methods used in this training include counselling, hands-on demonstrations, and interactive practical sessions, so that the participants can easily understand and apply sport massage in their daily lives. The results of this activity showed an increase in participants' knowledge and skills in performing sport massage, as well as increased awareness of the importance of a healthy lifestyle.